What Goes Around, Comes Around : Circular Economy Motivation in Finnish Companies - Valkjärvi, Mira (My University, 2019)
With the raise in concern for the environment and its rapid decline, this research focuses on the actions that firms may take to become more environmentally friendly. The research topic specifically focuses on circular economy and the reasons that Finnish publicly listed companies have adapted circular economy related practices in their business operations. The purpose of this research is to identify the underlying motivations that push companies towards circular economy. Extant literature for circular economy and motivation theories was reviewed in this research, which helped to shape a framework of company motivation for circular economy. The empirical research takes a qualitative approach with the use of case studies. Content analysis was firstly used to analyze secondary data derived from Finnish publicly listed firms’ annual reports, CSR and sustainability reports, which formed the basis for case selection. Five case companies were selected for the research and data was collected in the form of semi-structured in-depth interviews. Within-case and cross-case analysis was conducted for the analysis of the interview data. The research identified eight major factors of motivation and developed further the framework of company motivation to adapt circular economy practices. These eight factors include: cultural context, service logic, ease of transition to other countries, profitability of waste management, symbiotic partnerships, legislative impact, marketing related issues, and a call to researchers to simplify the sustainability field. This research contributes to the literature streams of circular economy and motivation theories by applying motivation theories in the circular economy context.
Keywords: circular economy, motivation